2012
DOI: 10.1111/j.1399-3054.2012.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the sweetpotato R2R3‐type IbMYB1a gene induces anthocyanin accumulation in Arabidopsis

Abstract: R2R3-type MYB transcription factors (TFs) play important roles in transcriptional regulation of anthocyanins. The R2R3-type IbMYB1 is known to be a key regulator of anthocyanin biosynthesis in the storage roots of sweetpotato. We previously showed that transient expression of IbMYB1a led to anthocyanin pigmentation in tobacco leaves. In this article, we generated transgenic Arabidopsis plants expressing the IbMYB1a gene under the control of CaMV 35S promoter, and the sweetpotato SPO and SWPA2 promoters. Overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 44 publications
0
52
0
Order By: Relevance
“…Anthocyanins were extracted and measured using the method described by Chu et al (2012). All samples were measured in triplicate from two independent biological replicates.…”
Section: Extraction and Quantification Of Anthocyanins And Flavonoidsmentioning
confidence: 99%
“…Anthocyanins were extracted and measured using the method described by Chu et al (2012). All samples were measured in triplicate from two independent biological replicates.…”
Section: Extraction and Quantification Of Anthocyanins And Flavonoidsmentioning
confidence: 99%
“…Total anthocyanins were extracted from 0.1 g of finely ground flower tissue and measured spectrophotometrically at the wavelengths 530 and 657 nm as described by Chu et al (2013).…”
Section: Measurement Of Anthocyanin Contents By Spectrophotometrymentioning
confidence: 99%
“…As a general strategy, transcriptionally activating the upstream pathway might increase the metabolic flux of intermediates and provide more substrates. We previously reported (Chu et al 2013;) that overexpression of IbMYB1a in Arabidopsis and tobacco plants led to anthocyanin pigmentation through the transcriptional activation of structural genes in the anthocyanin biosynthetic pathway. Moreover, in the present study, we noted that the biosynthetic genes encoding PAL, C4H, and 4CL enzymes in the phenylpropanoid pathway were upregulated by IbMYB1a expression (Fig.…”
mentioning
confidence: 98%
“…Recently, Park et al (2015) reported that overexpression of IbMYB1a in a single orange-fleshed sweetpotato cultivar generated dual-pigmented transgenic plants with high levels of both anthocyanins and carotenoids in their storage roots. In addition, the expression of IbMYB1a alone was sufficient for heterologous activation of anthocyanin biosynthesis in transiently agro-infiltrated tobacco leaves and stably transformed Arabidopsis plants (Chu et al, 2013;Kim et al, 2010;Mano et al, 2007). Identifying the interacting partners of IbMYB1a TF is necessary for elucidating the gene regulatory networks controlling anthocyanin biosynthesis in purple-fleshed sweetpotato.…”
mentioning
confidence: 97%